Immunomodulation with β-glucan in matrinxã (Brycon amazonicus) - Franco-Montoya, Luz Natalia [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This study was performed through three experiments and is presented in six chapters. In the first, we present a general introduction on the subject of the thesis and in the last chapter we present the final considerations and thesis conclusions. The other four chapters were written as scientific papers to be submitted to specialized journals. In the first experiment, we tested the innate immune response of juvenile matrinxã Brycon amazonicus fed with two concentrations of β-glucan (β-G) derived from Saccharomyces cerevisiae (0.5% and 1.0%) during 10 days. After feeding, we experimentally infected the fish with an intraperitoneal (IP) injection of Aeromonas hydrophila and sampled the animals prior to and 6 h post infection (hpi). The results showed that β-glucan (0.5%) improved the pre-infection cortisol and lysozyme serum levels and modulated some acute phase proteins on the acute phase response of fish. In addition, we observed that β-glucan (1.0%) led to the exhaustion of innate immune response and can be detrimental to health of fish. In the second experiment, we evaluated two generations of β-glucan, with different levels of purity: MacroGard (β-G 1° 71% pure) and a new generation “R&D β-glucan” (β-G 2° 62% pure). Two groups of fish were supplemented during 15 days with 0.1% of respective generations of β-glucan and at the end of trial fish were challenged with IP injection of A. hydrophila. Fish were sampled prior to, 6, 24, and 72 hpi. Data from this experiment is presented in chapters 3 and 4 of this thesis. The results showed that β-G 2° was more efficient to stimulate both humoral and cellular innate immune responses in fish. However, both β-glucan generations showed an ability to increase pre-infection cortisol and lysozyme serum levels as well as increase the number of circulating neutrophils and monocytes. In addition, the use of β-G 2° was observed to modulate the serum protein profile during acute phase respo nse by bacterial infection of fish. In the third experiment, we discussed the role of serum cortisol levels on the immunostimulant effect of β-glucan. To this end, we fed fish during 15 days with diets containing β-glucan 0.1% only (β-G) or β-glucan 0.1% + metyrapone 30mg kg -1 fish (β-G+MTP). Dietary MTP was used to block the cortisol production. The fish were then submitted to 3 min of air exposure as an acute stressor and , following that, challenged with an IP injection of A. hydrophila. Fish were sampled prior to stress conditions, 30 min after stressor exposure and 24 hpi. The results showed that β -G modulated the cortisol profile prior to and after stress response, and increased both the number and activity of leukocytes. Furthermore, cortisol was shown to be a strong modulator of both humoral and cellular innate immune mechanisms, since it increased the lysozyme and complement activity as well as the neutrophils and monocytes populations. Our results suggest that β-glucan-induced cortisol level is one important mechanism to improve the innate immune response to β-glucans in matrinxã. Finally, we propose a protocol of immunestimulation for juvenile matrinxã. The addition of β-glucan derived from the cell wall of Saccharomyces cerevisiae can be offered to the fish before management practices. The proposed protocol aims to strengthen fish defense mechanisms, reduce disease outbreak and enhance fish resistance, generating a nutritional product of high quality and safety.

Este estudo foi feito por meio de três experimentos e é apresentado em seis capítulos. No primeiro, apresentamos uma introdução geral sobre o tema da tese e no último as considerações finais. Os capítulos restantes foram escritos como artigos científicos. No primeiro experimento, foi avaliada a resposta imune inata de juvenis de matrinxã Brycon amazonicus alimentados com duas concentrações de β-glucano (β-G) derivado de S. cerevisiae (0,5% e 1,0%) durante 10 dias. Depois da alimentação, os peixes foram infectados experimentalmente com injeção intraperitoneal (IP) de A. hydrophila. Os peixes foram amostrados antes e 6 h após a infecção (hpi). Os resultados mostraram que o β-G (0,5%) aumentou os níveis de cortisol sérico e da lisozima antes da infecção e modulou algumas proteínas de fase aguda na resposta imune do matrinxã. Além disso, observamos que 1,0% de β-G na dieta provocou exaustão da resposta imune inata e pode ser prejudicial para a saúde de peixes. O segundo experimento avaliou a inclusão de duas gerações de β-G na dieta, com diferentes níveis de pureza: MacroGard (β-G 1° 71% puro) e uma nova geração do produto "R&D β-glucano" (β-G 2° 62% puro). Os peixes foram alimentados por 15 dias com 0,1% de cada tipo de β-G e depois desafiados com injeção IP de A. hydrophila. Os peixes foram amostrados antes, 6, 24, e 72 hpi. Com os dados deste experimento foram escritos os capítulos 3 e 4. Os resultados mostraram que o β-G 2 ° foi mais eficiente para estimular a resposta humoral e celular do sistema imune inato. No entanto, ambas as gerações de β-G aumentaram o cortisol pré-infecção os níveis séricos de lisozima, e o número de neutrófilos e monócitos circulantes. A utilização do β-G 2 ° modulou o perfil de proteínas de soro durante a infecção bacteriana. No terceiro experimento, avaliamos o papel do cortisol na ação imunestimulante do β-glucano. Neste sentido, peixes foram alimentados por 15 dias com dietas que continham Macrogard β-G (0,1%) ou β-G (0,1%) + metirapona (MTP). A MTP foi usada para bloquear a produção do cortisol. Em seguida, os peixes foram submetidos a 3 min de exposição aérea como estressor agudo e logo após desafiados com A. hydrophila. Os peixes foram amostrados antes do estresse, 30 min após a exposição ao estressor e 24 hpi. Os resultados mostraram que o β-G modulou o perfil de cortisol antes e depois da resposta de estresse e aumentou o número e a atividade dos leucócitos. Observamos um forte efeito modulador do cortisol nos mecanismos humorais e celulares da imunidade inata do matrinxã, pois aumentou os níveis de lisozima e a atividade do sistema complemento, bem como as populações de neutrófilos e monócitos. O nosso resultado sugere que o aumento do cortisol induzido pelo β-G é um importante mecanismo para melhorar a resposta imune inata promovida por β-G em matrinxã. Finalmente, nós propomos um protocolo de imunestimulação para juvenis de matrinxã pela suplementação com o β-G de S. cerevisiae fornecido dias antes das práticas de manejo estressantes. Este protocolo visa reforçar os mecanismos de defesa immune, reduzir surtos de doenças e aumentar a resistência dos peixes, gerando um produto nutricional de alta qualidade e segurança.
Inmunomodulación con β-glucan en matrinxã (Brycon amazonicus)
Keywords: Humoral and cellular immunity; Early immune defense; Stress; Infection; Imunidade humoral e celular; Defesa precoce; Estresse; Infecção